Arthroscopic treatment and mid-term results of suprapatellar plica syndrome: a single-center experience of 14 cases - Aydın, Murat; Çınaroğlu, Selim (The European Research Journal, 2022)
Objectives: Synovial plicae syndrome (SPS) are encountered as a mesenchymal tissue remnant during the process of embryological development, and divide the knee joint into three separate compartments. Of these, the suprapatellar plica may be affected by a syndrome that manifests with anterior knee pain, a clicking sound, snagging and a feeling of skipping after a patellofemoral overload. The present study evaluates 14 patients with suprapatellar complete plica syndrome who were treated between 2013 and 2019, and discusses the medical and surgical medium-term results of the condition. Methods: Included in the study were 225 cases who underwent knee arthroscopy between 2013 and 2019, the data of which were analyzed retrospectively. The exclusion criteria were accompanying meniscal tear, anterior and posterior cruciate ligament tears, chronic inflammatory arthritis, varus > 3˚ and valgus > 5˚ malalignments. The cases were followed-up using the Tegner Lysholm knee scoring method, during the preoperative period, in the postoperative period, and in postoperative week 12 and month 6. The statistical analysis was performed using the IBM SPSS Statistics (Windows Version 25.0. Armonk, NY: IBM Corp.) software package. Results: A retrospective analysis revealed a BMI of 28.7 ± 5.6 kg/m2 in the 14 cases. The mean age was 34.57 ± 8.53 years. Intraarticular cortisone injections and intraarticular viscosupplementations were performed at the outpatient follow-up in eight and three cases, respectively. Furthermore, eight cases had undergone previous physical therapy and rehabilitation. The mean duration of symptoms was 1.4 ± 0.8 months. The Tegner Lysholm knee scores were 69.53 ± 6.15, 88.23 ± 3.00, and 93.76 ± 3.83 in the preoperative period, week 12 and month 6, respectively. Conclusions: In conclusion, arthroscopy can be considered an efficacious and diagnostic method in knee plica syndrome. Patient satisfaction is high in the medium-term.